INEFFICIENT USE OF PESTICIDFS AND WELFARE LOSS ASSOCIATED WITH NEGATIVE EXTERNALITY IN INDONESIAN RICE AGRICULTURE - Mariyono, Joko (Jurnal Ekonomi & Studi Pembangunan, 2006)
Pesticides provide economic benefits for the farmers in terms of saving yield loss: but also provide adverse impacts. It is therefore economically inefficient to totally ban the use of pesticides; and consequently, it is required to investigate an efficient level of pesticide use. This paper aims to determine the efficient use of pesticides by internalizing the externality costs, and estimates the monetary value of net welfare loss. The benefit of pesticide use is estimated using a production function and the economic value of the adverse impact on human health and the environment are represented by a health Cost and consumers’ willingness to pay for a kilogram reduction in pesticide use. Panel data on rice production used in this paper is compiled from publication of Indonesian Statistics Agency. The externality costs including are adopted and adjusted from previous researches. The socially efficient use of pesticides is determined when the marginal benefit is equal to the marginal social cost. The results of this study indicated that the efficient use of pesticides is lower than that of actual use. Consequently, there is welfare loss imposed on farmers and other community. The policy implication is that it is preferable for the farmer to use pesticide efficiently.